Some Genetic Variation Parameters of Iraqi Sheep Population Using SSR Markers in Babylon City - Hayder R. Alnajm; Arash Javanmard (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2024)
This study focuses on designing a conservation indigenous Awassi sheep breeding program based on the analysis of genetic variation using the simple sequence repeat markers (SSR). The allele frequency distribution of six SSR markers distributed on three different chromosomes was used to determine the genetic variation among 50 Awassi sheep (15 from the north, 20 from the middle, and 15 from the south of Babylon city) that were collected from the private herds. The results showed that the RM32 marker exhibited high frequency and the most genotypes existed compared to other markers. The mean number of alleles (NA), the effective number of alleles (NE), the Shannon index (I), and the polymorphism information content (PIC) values per loci were 2.66 ± 0.81, 2.05 ± 0.87, 0.73 ± 0.42, and 0.37± 0.26 respectively. Also, the average observed (Obs_Hom), expected (Exp_Hom) homozygosity, observed (Obs_Het), expected (Exp_Het) heterozygosity, Nei’s expected heterozygosity, and inbreeding coefficient (FIS) were 0.77± 0.18, 0.56 ±0.25, 0.23 ± 0.18, 0.44 ±0.25, 0.43± 0.24, and 0.41± 0.12, respectively. The results of the Bayesian analysis revealed that all populations were homogenous there was a clear overlap between the individuals of the three distinct clusters were formed. On this basis, we conclude that the indigenous Awassi sheep in Babylon city have reasonable genetic variation.